What is a visual language?. (February 2017) - Erwig, Martin; Smeltzer, Karl; Wang, Xiangyu
Abstract: The visual language research community does not have a single, universally agreed-upon definition of exactly what a visual language is. This is surprising since the field of visual languages has been a vibrant research area for over three decades now. Disagreement about fundamental definitions can undermine a field, fragment the research community, and potentially harm the research progress. To address this issue we have analyzed two decades of VL/HCC publications to clarify the concept of "visual language" as accepted by the VL/HCC community, effectively adopting the approach of descriptive linguistics. As a result we have obtained a succinct visual language ontology, which captures the essential aspects of visual languages and which can be used to characterize individual languages through visual language profiles. These profiles can tell whether and in what sense a notation can be considered a visual language. We also report trends from and statistics about the field of visual languages.